Circulating Th1 and Th2 Subset Accumulation Kinetics in Septic Patients with Distinct Infection Sites: Pulmonary versus Nonpulmonary - Ming Xue; Yuying Tang; Xu Liu; Mingyuan Gu; Jianfeng Xie; Ling Liu; Yingzi Huang; Fengmei Guo; Yi Yang; Haibo Qiu (Mediators of Inflammation)
Background. Persistent peripheral CD4+T cell differentiation towards T helper (Th)2 rather than Th1 has been proved to be related to immunosuppression and poor prognosis in sepsis. However, it is unclear whether these circulating Th1 and Th2 subtype accumulations differed in septic populations of distinct infection sites and presented different associations with outcomes among patients with pulmonary versus nonpulmonary sepsis. Methods. From a secondary analysis of a prospective observational study, seventy-four previously immunocompetent patients with community-acquired severe sepsis within 24 hours upon onset were enrolled. Whole blood was collected on the admission day (D0), 3rd day (D3), and 7th day (D7). The patients were classified as pulmonary (n=52) and nonpulmonary sepsis (n=22). Circulating Th1 and Th2 populations were evaluated by flow cytometry, and clinical data related to disease severity and inflammatory response were collected. The associations of circulating Th1 and Th2 subset accumulations with distinct infection sites or outcomes within subgroups were explored. Results. Patients with pulmonary sepsis held similar disease severity and 28-day mortality with those of nonpulmonary sepsis. Of note is the finding that circulating Th2 levels on D7 (P=0.04) as well as Th2/Th1 on D3 (P=0.01) and D7 (P=0.04) were higher in the pulmonary sepsis compared with nonpulmonary sepsis while Th1 levels were lower on D0, D3, and D7 (P=0.01, <0.01, and =0.05, respectively). Compared to 28-day survivors, higher Th2/Th1 driven by increased Th2 were observed among 28-day nonsurvivors on D3 and D7 in both groups. The association between circulatory Th2 populations or Th2/Th1 and 28-day death was detected in pulmonary sepsis (P<0.05, HR>1), rather than nonpulmonary sepsis. Conclusions. Circulating Th2 accumulation was more apparent among pulmonary sepsis while nonpulmonary sepsis was characterized with the hyperactive circulating Th1 subset among previously immunocompetent patients. This finding suggested that circulating Th1 and Th2 subset accumulations vary in septic subgroups with different infection sites.